Nuclear DNA base composition and base sequence complementarity of recently described candida species and strains of selected species / Tengku Elida Tengku Zainal Mulok - Tengku Zainal Mulok, Tengku Elida (Universiti Teknologi MARA, Pahang, 1991)
As early as 1970, it was pointed out that conventional methods were not adquate to differentiate species of yeasts. However, species are still described without deoxyribonucleic acid (DNA) base complementarity studies. The definitions of yeast species and genera have been principally on the basis of morphological and physiological characters, and many of these appear to be unreliable indicators of kinship. In this investigation, ten recently decribed Candida species were examined and strains of selected species were also evaluated. These strains were characterized by physiological and morphological studies. The base composition of DNA, expressed in molar percent of guanine plus cytosine (%G+C), of each strain was also determined. Nuclear DNA base sequence complementarity of these strains and physiologically similar strains were also examined in an effort to clarify the taxol1omic status of the newly described species and strains of known Candida species. By using this method, it was found that: (a) four new species have no significant relatedness with known species, although these strains have similar physiological characteristics and GC contents; (b) one strain of C. norvecica showed insignificant DNA relatedness with the type strain of C norvegica; (c) C. amidevorans is a synonym of C. guilliermondii since it showed a high degree of DNA relatedness with one of the mating types of f. guilliermondii; (d) two strains identified as C. milleri showed a high degree of DNA relatedness with the type strain of C. milleri. thus proving the status of these two strains are species of C. milleri. (e) two strains identified as C. oleophila showed insignificant DNA relatedness with the type strain of C. oleophila and the type strain of C. sake, showing that these two strains do not belong to either species; (f) one strain of Pichia stipitis and the three strains of C. shehatae showed a high degree of homol ogy with the type strain of each species; (g) the proposition of P. stipitis being the perfect counterpart of C. shehatae has to be rejected since insignificant DNA relatedness was demonstrated between strains of C. shehatae and the type strain of F. stipitis. In conclusion the determination of base composition is very helpful in obtaining further clues to, or supporting evidence to estimate the relatedness of morphologically and physiologically similar organisms; but it alone is insiginficant in assessing relatedness. DNA base complementarity provides the most useful means of evaluation and comparing yeast genomes.